Exploring the Role of C-C Motif Chemokine Ligand-2 Single Nucleotide Polymorphism in Pulmonary Tuberculosis: A Genetic Association Study from North India - Sanjay K. Biswas; Mayank Mittal; Ekata Sinha; Vandana Singh; Nidhi Arela; Bharat Bajaj; Pramod K. Tiwari; Vishwa M. Katoch; Keshar K. Mohanty (Journal of Immunology Research)
The C-C motif chemokine ligand-2 (CCL2) was evidenced to be associated with tuberculosis susceptibility in some ethnic groups. In the present study, effort was made to find out the association of CCL2-2518 A>G and -362 G>C variants with susceptibility to TB in a population from North India. The genotyping was carried out in 373 participants with pulmonary TB (PTB) and 248 healthy controls (HCs) for CCL2-2518 A>G and -362 G>C polymorphisms by PCR-RFLP and by melting curve analysis using fluorescence-labeled hybridization fluorescent resonance energy transfer (FRET) probes, respectively, followed by DNA sequencing in a few representative samples. Genotype and allele frequencies were compared by the chi-squared test and crude and Mantel-Haenszel (M-H) odds ratio (OR). OR was calculated using STATA/MP16.1 software. Further, CCL2, IL-12p70, IFN-γ, TNF-α, and TGF-β levels were measured in serum samples of these participants using commercially available kits. Our analysis indicated that the homozygous mutant in both -2518 GG (OR=2.07, p=0.02) and -362 CC (OR=1.92, p=0.03) genotypes was associated with susceptibility to pulmonary TB. Further, heterozygous genotypes -2518AG (OR=0.60, p=0.003) and -362GC (OR=0.64, p=0.013) provide resistance from PTB disease. Haplotype analysis revealed AC haplotype (p=0.006) to be a risk factor associated with PTB susceptibility. The serum CCL2 level was significantly elevated among participants with -2518 AA genotype compared to -2518 GG genotype. CCL2 level was observed to be positively correlated with IL12p70, IFN-γ and TNF-α, thus suggesting the immunological regulatory role of CCL2 against pulmonary tuberculosis. CCL2-2518 GG and -362 CC genotypes were found to be associated with susceptibility to pulmonary tuberculosis and CCL2-2518AG and CCL2-362GC with resistance from PTB. AC haplotype was found to be a risk factor for PTB in the present study. It may be hypothesized from the findings that -2518G allele could be responsible for lower production of CCL2 which leads to defective Th1 response and makes a host susceptible for pulmonary tuberculosis.